International Market Access and Poverty in Argentina - Guido Porto (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2010)
This paper examines the impact of access to international agro-manufacture markets on poverty in Argentina. Measures of international market access, such as cuts in tariffs and abolition of non-tariff measures, can be approximated by changes in the price of key exportable goods. Estimates from the related literature suggest that expanded market access would cause the international price of Argentine exports of agro-manufactures to increase by between 7.5 and 15.4 percent. I explore two poverty effects caused by these prices changes: on food expenditure and on wages. Using a household budget survey, I estimate the impact of higher food prices on the Argentine poverty line. Using a labor force survey, I estimate the responses of wages to changes in export prices. My main finding is that market access would cause poverty to decline in Argentina. From a national head count of 29.3 percent, the poverty rate would decline to between 27.9 and 28.5 percent. This means that between 280,000 and 490,000 Argentines would be moved out of poverty. – Doha Round Trade reforms ; Net exports in agriculture ; Household real income
Keywords: F14; F16; F17; 330; Export; Agraraußenhandel; Lebensmittel; Agroindustrie; Armut; Argentinien